PENGGUNAAN MEBEL TAMIA DALAM PEMBELAJARAN MENULIS TEKS DESKRIPSI BANGUNAN BERSEJARAH KOTA PASURUAN - Fika Rahmawati (FKIP, Universitas Billfath Lamongan, 2020)
21st century learning is characterized by digital media used in the learning process or often called the industrial revolution 4.0. The use of digital media in the 21st century does not mean that conventional media is not good or suitable for use in learning. When teachers can make the most of these media, conventional media can also bring their own positive values to students. Like learning to write description text. The learning process of this material can use conventional media such as Tamia Furniture. Furniture Tamia stands for Taman Learning Miniature Media can help students in the learning process of writing description texts in the form of historical buildings in Pasuruan City.